Desenvolvimento rural do semiárido brasileiro: transformações recentes, desafios e perspectivas - Antonio Marcio Buainain; Junior Ruiz Garcia (Confins)
Brazilian Semiarid Rural Development: recent transformations, challenges and prospects- Brazilian Semiarid has been characterized as a problem region in Brazil. Although rich in natural resources, the Semiarid faces severe ecological constraints, mostly associated with periodic occurrence of severe drought that leaves a trail of poverty and dismay. It is identified by social, economic and political backwardness, and known as the land of “coronéis”, which symbolize the institutional backwardness that has been dominant in the region over the centuries. Currently the Semiarid concentrates the largest share of Brazilian rural population living in poverty and extreme poverty conditions. Although this picture is still partially true, it does not take into account a “new” scenario that is emerging in this region fostered by public and private investments in infrastructure, industries, mines and agriculture, and by social policies as well. In the recent period, the Northeast Region, the Semiarid included, has benefited from a wide range of initiatives of the federal government, which are generating numerous positive effects that have the potential to transform the structures of the Semiarid and insert it into a virtuous cycle accumulation. The results of this intervention are still uncertain, especially in rural areas, where massive poverty does hinder, and maybe block at all, the inclusion of large share of the population into the new wave of development and opportunities created by these investments. The main goal of this paper is to discuss the challenges and prospects for overcoming rural poverty and promoting development in Brazilian Semiarid. Besides, the paper presents a broad socioeconomic picture of the region and discusses some of the key changes underway. The analysis draws from Brazilian government’s documents and academic studies, and is based on collection and processing of statistical data with the assistance of GIS (Geography Information System) techniques. The spatialization of socioeconomic indicators by municipality revealed marked heterogeneity and indicates that rural poverty is not homogeneous across the region. This paper proposes that a three-pillars strategy to combat rural poverty. The first one is to protect the poor population by reducing exposure to severe insecurities which have undermines the potentialities of the poor throughout their lives. The second one is to interrupt the reproduction of poverty, preventing that poor childhood of today is poor youth of tomorrow, and the poor youth of today is the head of a new poor domicile. Finally, the third one is inserting the rural poor in the chains of production and generating of wealth, so that they can generate enough income to take up their strategies lives autonomously. This strategy involves specifics goals, different temporal dimensions, differentiate scope and focus; it requires high politic and operational capacity to coordinate actions in many areas and to implement both universal and more selective policies, which imply in hard choices by the government.